An ultrafast carbon nanotube terahertz polarisation modulator - Docherty, C; Stranks, S; Habisreutinger, S; Joyce, H; Herz, L; Nicholas, R; Johnston, M (American Institute of Physics, 2014)
We demonstrate ultrafast modulation of terahertz radiation by unaligned optically pumped single-walled carbon nanotubes. Photoexcitation by an ultrafast optical pump pulse induces transient terahertz absorption in nanowires aligned parallel to the optical pump. By controlling the polarisation of the optical pump, we show that terahertz polarisation and modulation can be tuned, allowing sub-picosecond modulation of terahertz radiation. Such speeds suggest potential for semiconductor nanowire devices in terahertz communication technologies.